EVALUASI IMPLEMENTASI PEMBELAJARAN STUDENTS CENTERED LEARNING OLEH MAHASISWA PPL FKIP-UKI DI SEKOLAH MITRA – PSKD - Eden Handayani Tyas; Sunarto Sunarto; Lamhot Naibaho (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
This study is about the evaluation of student centered learning implementation by Internship students of Faculty of Education and Teacher Training at PSKD Jakarta. The purpose of this study to find out how the implementation of student centered learning at the school. The research method used was survey method by using qualitative research approach. The respondents of this study were 31 teachers who were taken using proportional random sampling (50%) from 62 companion teachers. The instruments used in this study were questionnaires (which consists of 24 statements) and interviews. Questionnaire data was analyzed quantitatively by classification of Likert scale value while interview data was analyzed descriptively. From the data collected through questionnaires and interviews found that the implementation of student centered learning in PSKD partner schools in Jakarta is good, and 30% of teachers still believe that the implementation of student centered learning in PSKD partner schools is still poor. Thus, it can be concluded the implementation of students centered learning at PSKD is good, but it still needs improvement. Keyword: evaluation, implementation, students centered learning, PPL